Analysis of the global burden of diabetes and attributable risk factor in children and adolescents across 204 countries and regions from 1990 to 2021 - Hu, Yu; He, Tingting; Zhang, Yu; Long, Yang; Gao, Chenlin; Xu, Yong (Frontiers in Endocrinology, 2025)
BackgroundWhile middle-aged and elderly individuals account for the majority of diabetes cases, recent years have witnessed a rising incidence of diabetes, particularly type 2 diabetes, among younger populations. This study aims to examine global trends in diabetes among children and adolescents (<20 years) across 204 countries and regions.MethodsThis study draws primarily from the 2021 GBD database, offering an in-depth analysis of trends in the incidence, mortality, and disability-adjusted life years (DALYs) of diabetes in children and adolescents from 1990 to 2021, with further subgroup analyses conducted by sex, age, and specific regions. Furthermore, we investigated the potential risk factors contributing to diabetes-related mortality in children and adolescents.ResultsBetween 1990 and 2021, the global incidence of diabetes among children and adolescents exhibited a steady upward trend. By 2021, the incidence of diabetes had risen by approximately 94.0% compared to 1990, while both mortality and DALYs experienced a notable decline. Subgroup analyses region revealed that death rates were generally lower in regions with a high sociodemographic index (SDI) compared to those with a low SDI and low income. Additionally, high fasting blood glucose, along with extreme temperature conditions (both high and low), were identified as the three major risk factors contributing to diabetes-related mortality in children and adolescents.ConclusionsWhile diabetes-related mortality in children and adolescents has declined over time, the sharp increase in incidence indicates that it is emerging as a major threat to global child and adolescent health.